INVESTIGATING THE KINEMATICS OF THE COVERING UNIT IN A MACHINE DESIGNED FOR THE CONTINUOUS PLANTING OF FRUIT TREE SAPLINGS (American AgriTech: Journal of Agricultural Technology Innovation and Sustainability, 2026)
This study presents a theoretical investigation of the kinematic behaviour of the covering unit in a machine designed for continuous planting of fruit tree saplings. In existing planting practices, soil preparation and sapling covering are performed as separate operations, with the covering process predominantly carried out manually, leading to increased labour intensity and operational costs. To improve efficiency, a continuous planting machine integrating furrow opening, sapling placement, soil covering, and compaction into a single technological process is considered. The research focuses on the kinematic analysis of the covering unit, which performs combined rotational motion about its axis and translational motion along with the machine. The motion of points on the working surface is described within a three-dimensional Cartesian coordinate system. Analytical expressions for velocity and acceleration are derived, enabling evaluation of the influence of key parameters such as operating speed, unit diameter, installation angle, and curvature radius on the soil covering process
Keywords: Fruit tree saplings; planting machine; covering unit